S100A9 is a biliary protein marker of disease activity in primary sclerosing cholangitis - Reinhard, Lisa Marlene; Rupp, Christian; Riedel, Hans-Dieter; Ruppert, Thomas; Giese, Thomas; Flechtenmacher, Christa; Weiss, Karl Heinz; Stremmel, Wolfgang; Schirmacher, Peter; Sauer, Peter; Gotthardt, Daniel (PLOS ONE, 2012)
Background and Aims Bile analysis has the potential to serve as a surrogate marker for inflammatory and neoplastic disorders of the biliary epithelium and may provide insight into biliary pathophysiology and possible diagnostic markers. We aimed to identify biliary protein markers of patients with primary sclerosing cholangitis (PSC) by a proteomic approach. Methods Bile duct-derived bile samples were collected from PSC patients (n = 45) or patients with choledocholithiasis (n = 24, the control group). Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was performed to analyse the proteins, 2-D-gel patterns were compared by densitometry, and brush cytology specimens were analysed by RT-PCR. Results A reference bile-duct bile proteome was established in the control group without signs of inflammation or maligancy comprising a total of 379 non-redundant biliary proteins; 21% were of unknown function and 24% had been previously described in serum. In PSC patients, the biliary S100A9 expression was elevated 95-fold (p<0.005), serum protein expression was decreased, and pancreatic enzyme expression was unchanged compared to controls. The S100A9 expression was 2-fold higher in PSC patients with high disease activity than in those with low activity (p<0.05). The brush cytology specimens from the PSC patients with high disease activity showed marked inflammatory activity and leukocyte infiltration compared to the patients with low activity, which correlated with S100A9 mRNA expression (p<0.05). Conclusions The bile-duct bile proteome is complex and its analysis might enhance the understanding of cholestatic liver disease. Biliary S100A9 levels may be a useful marker for PSC activity, and its implication in inflammation and carcinogenesis warrants further investigation.